Family Coping Strategies in Response to Adolescent Depression: A Study of Low-Resource Settings in Kisumu County, Kenya - MacDonald Odhiambo Owuor; Wilson Otengah; Michael Ntabo Mabururu; Taji Shivachi, (African Journal of Education,Science and Technology (AJEST), 2025)
Families are witnessing a high prevalence of adolescent depression, possibly because of a weakened societal fabric. It impairs psychosocial functioning and affects the normal activities of adolescents and families. While it is treatable, its prevalence implies inadequacy of available mitigations, attributable to comparatively high cost and shortage of mental health professionals. This suggests that some families may be forced to adopt alternative measures, which have hardly been documented, yet may be beneficial. Guided by Family Resilience Theory, the family coping strategies in response to adolescent depression in low-resource settings were explored. Using an exploratory cross-sectional design, both qualitative and quantitative data were collected from purposively selected parents of depressed 10-19-year-olds as main respondents and key informants comprising psychiatrists, counsellors, and clinical psychologists. Validity and reliability were ensured at a threshold of .88 and .80, respectively. Ethical considerations were ensured. Coping strategies adopted by families were spending time together, praying, and seeking hospital-based treatment. There were reservations seeking non-professionals' help. Study concludes that praying is linked to better adolescent depression outcomes (r = –.281**, p = .001); contrary to hospital-based treatment (r = .198**, p = .024), due to the existence of barriers to timely and effective treatments. Therefore, there is a need to upscale training programs for primary healthcare providers and community health promoters.